Revision of Mesozoic Myodocopina (Ostracoda) and a new genus and species, Mesoleberis hollandica, from the Upper Cretaceous of Belgium and The Netherlands - Kornicker, Louis S.; van Bakel, Barry W.m.; Fraaije, René H.b.; Jagt, John W.m. (Zootaxa, 2006)
Although Paleozoic strata have produced many ostracode fossils in the suborder Myodocopina, which are also abundant in today’s seas, their record is extremely sparse in Mesozoic strata. A new genus and species of myodocopid, Mesoleberis hollandica, from the upper Maastrichtian (Upper Cretaceous) of the southeast Netherlands and nearby Belgium is described herein. In addition, brief supplementary descriptions and illustrations are presented of other Myodocopina that have been reported from Mesozoic deposits; many of those species are referred to different genera, and six are placed in the category “species nomina dubia.”